KERAGAMAN BAKTERI ENDOFITIK DnSOLASI DARI EMPAT VARIETAS PADI DENGAN METODA ARDRA - Dwi N Susilowati; Nurul Hidayatun; Tasliah Tasliah; K Mulya (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Sixty eight endophytic bacteria were isolated from four different rice varieties (IR64, Cirata, Code and Limboto) obtained from agroecosystem in Cikembar, Sukabumi, West Java. Those isolates were subjected for analysis the diversity based on genetic fingerprinting through Amplified Ribosomal DNA Restriction Analysis (ARDRA) method. The objective of this research is to characterize the predominant endophyte bacteria are present within various rice varieties grown on agroecosystem in Cikembar, Sukabumi by using ARDRA method. The results shows that restriction analysis with both Rsal and HaelH was sufficient to allocate the endophyte bacteria from four different rice varieties into the 29 types. Moreover, Rsal alone was capable of resolving the 11 types, followed by HaelH 14 types. In general, the result may explain that there is no collinierity between the cluster and their host plant. Staphylococcus, Bacillus, Agrobacterium, Serratia, Klebsiella, Acidovorax and Pseudomonas were identified as endophytic bacteria from rice varieties in this agroecosystem based on their 16S rRNA sequences. Seven types were placed in close proximity to these genera, but other types were still unknown. Among these isolates, genera Staphylococcus and Bacillus are common to rice endophytes.